2017
DOI: 10.1186/s12893-017-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

ACDF vs TDR for patients with cervical spondylosis – an 8 year follow up study

Abstract: BackgroundACDF has been considered as the gold standard in the treatment of single level cervical disk protrusion. However, it may cause adjacent level degeneration due to regional biomechanical changes. TDR has been applied with satisfactory results for over a decade, but there is no consensus if TDR is safer and more efficient than ACDF. The current study was carried out to compare the efficiency and safety of TDR and ACDF in the treatment of patients with single level cervical disk protrusion.MethodsOne hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The concept of preserving the range of motion on the operating level is seducing. CDA may decrease the rate of ASD and of adjacent level surgery compared to ACDF [12,43,44].…”
Section: Cervical Disc Arthroplastymentioning
confidence: 99%
“…The concept of preserving the range of motion on the operating level is seducing. CDA may decrease the rate of ASD and of adjacent level surgery compared to ACDF [12,43,44].…”
Section: Cervical Disc Arthroplastymentioning
confidence: 99%
“…Surgical times for the 2 procedures have not appeared to be significantly different. 3 In fact, for patients with the 2-level disease, CDA had better patient outcomes, less perioperative complications, reoperations, and ASD without a longer operative time. 5 In summary, multiple studies have demonstrated that CDA is a reasonable treatment option in patients with cervical myelopathy, with similar outcomes to that of ACDF.…”
mentioning
confidence: 94%
“…Recently, long-term outcomes showed patients who underwent arthroplasty not only experienced improved patient-reported pain scores, but they also demonstrated preserved cervical motion during radiographic analysis at 8 years of follow-up. In addition, postarthroplasty motion was even increased when compared with preoperative motion in many patients 3…”
mentioning
confidence: 99%
“…Anterior cervical spine surgery, including anterior cervical discectomy and fusion (ACDF) and cervical total disc replacement (C-TDR), has proven to be an effective surgical procedure for the treatment of degenerative cervical disease. [1][2][3] This approach has various benefits, such as ventral pathology removal, nerve root decompression, and cervical lordosis restoration. 4,5 Proper disc space distraction and visualization are essential steps to achieve these benefits.…”
Section: Introductionmentioning
confidence: 99%